Ultra-high resolution and long scan depth optical coherence tomography with full-phase detection for imaging the ocular surface - Tao A (Dove Medical Press, 2013)
Aizhu Tao,1,3 Kristen A Peterson,2 Hong Jiang,1 Yilei Shao,1,3 Jianguang Zhong,1,4 Frank C Carey,2 Elias P Rosen,2 Jianhua Wang11Bascom Palmer Eye Institute, University of Miami, Miami, FL, USA; 2Southwest Sciences, Inc, Santa Fe, NM, USA; 3School of Ophthalmology and Optometry, Wenzhou Medical College, Wenzhou, Zhejiang, People's Republic of China; 4Department of Ophthalmology, Hangzhou First People's Hospital, Hangzhou, People's Republic of ChinaAbstract: We used a unique combination of four state-of-the-art technologies to achieve a high performance spectral domain optical coherence tomography system suitable for imaging the entire ocular surface. An ultra-high resolution, extended depth range, full-phase interferometry, and high-speed complementary metal-oxide semiconductor transistor camera detection provided unprecedented performance for the precise quantification of a wide range of the ocular surface. We demonstrated the feasibility of this approach by obtaining high-speed and high-resolution images of a model eye beyond the corneal–scleral junction. Surfaces determined from the images with a segmentation algorithm demonstrated excellent accuracy and precision.Keywords: ocular surface, complex, full range, optical coherence tomography